1988
DOI: 10.1021/bk-1988-0380.ch016
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids as Models for New Agrochemicals

Abstract: This chapter examines the evidence that some terpenoids serve as plant growth regulators (allelochemicals) as well as anti-herbivore agents. The plant origin and bioassay method of terpenoid allelopathic agents is explored. The role these same compounds play in plant-insect communication due to volatiles, and their involvement as insect pheromones is discussed. The agrochemical possibilities are far-reaching.Terpenes and terpenoids are ubiquitous in the higher plant kingdom. Although the role of these compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…Calcd. for C 22 H 30 O 5 : C, 70.56; H, 8.07; Found: C, 70.90; H, 8.01; IR n max /cm -1 3490, 3475, 2975, 2925, 2855, 1730, 1500, 1460, 1430, 1365, 1300, 1155, 1020, 715; 1 H NMR d 7.26 (d,3 J = 2.0 Hz, 1H, H-16), 6.18 (d, 3 J = 2.0 Hz, 1H, H-15), 4.15-4.30 (m, 2H, CH 2 -1'), 3.90 (dd, 3 J = 10.3 and 1.1 Hz, 1H, H-7), 3.59 (ddd, 3 J = 8.9, 2.9 and 1.7 Hz, 1H, H-14), 2.75 (ddd, 2 J = 16.3 Hz, 3 J = 5.8 and 1.7 Hz, 1H, H-11b), 2.50 (ddd, 2 J = 16.3 Hz, 3 J = 11.2 and 2.9 Hz, 1H, H-11a), 2.42 (ddd, 3 J = 12.2, 10.3 and 8.9 Hz, 1H, H-8), 2.17 (s, 1H, H-5), 1.96 (ddd, 3 J = 12.2, 11.2 and 5.8 Hz, 1H, H-9), 1.80 (dtd, 2 J = 13.2 Hz, 3 J = 3.2 Hz, 4 J = 0.9 Hz, 1H, H-1b), 1,64 (qt, 2 J = 13.2 Hz, 3 J = 13.2 and 3.2 Hz, 1H, H-2a), 1.55 (dqui, 2 J = 13.2 Hz, 3 J = 3.2 Hz, 1H, H-2b), 1.40 (dtd, 2 J = 13.2 Hz, 2 J = 3.2 Hz, 4 J = 0.9 Hz, 1H, H-3b), 1.32 (s, 3H, CH 3 -19), 1.29 (t, 3 J = 7.2 Hz, 3H, CH 3 -2'), 1.22 (td, 2 J = 13.2 Hz, 3 J = 13.2 and 3.2 Hz, 1H, H-1a), 1.10 (td, 1H, 2 J = 13.2 Hz, 3 J = 13.2 and 3.2 Hz, H-3a), 0.97 (s, 3H, CH 3 -18), 0.91 (s, 3H, CH 3 -20); 13 C NMR d 209.Propyl 7b-hydroxy-6-oxovouacapan-17b-oate (6): (171 mg, 88 %); white solid; m.p. 84.6-86.2 °C; Anal.…”
mentioning
confidence: 99%
“…Calcd. for C 22 H 30 O 5 : C, 70.56; H, 8.07; Found: C, 70.90; H, 8.01; IR n max /cm -1 3490, 3475, 2975, 2925, 2855, 1730, 1500, 1460, 1430, 1365, 1300, 1155, 1020, 715; 1 H NMR d 7.26 (d,3 J = 2.0 Hz, 1H, H-16), 6.18 (d, 3 J = 2.0 Hz, 1H, H-15), 4.15-4.30 (m, 2H, CH 2 -1'), 3.90 (dd, 3 J = 10.3 and 1.1 Hz, 1H, H-7), 3.59 (ddd, 3 J = 8.9, 2.9 and 1.7 Hz, 1H, H-14), 2.75 (ddd, 2 J = 16.3 Hz, 3 J = 5.8 and 1.7 Hz, 1H, H-11b), 2.50 (ddd, 2 J = 16.3 Hz, 3 J = 11.2 and 2.9 Hz, 1H, H-11a), 2.42 (ddd, 3 J = 12.2, 10.3 and 8.9 Hz, 1H, H-8), 2.17 (s, 1H, H-5), 1.96 (ddd, 3 J = 12.2, 11.2 and 5.8 Hz, 1H, H-9), 1.80 (dtd, 2 J = 13.2 Hz, 3 J = 3.2 Hz, 4 J = 0.9 Hz, 1H, H-1b), 1,64 (qt, 2 J = 13.2 Hz, 3 J = 13.2 and 3.2 Hz, 1H, H-2a), 1.55 (dqui, 2 J = 13.2 Hz, 3 J = 3.2 Hz, 1H, H-2b), 1.40 (dtd, 2 J = 13.2 Hz, 2 J = 3.2 Hz, 4 J = 0.9 Hz, 1H, H-3b), 1.32 (s, 3H, CH 3 -19), 1.29 (t, 3 J = 7.2 Hz, 3H, CH 3 -2'), 1.22 (td, 2 J = 13.2 Hz, 3 J = 13.2 and 3.2 Hz, 1H, H-1a), 1.10 (td, 1H, 2 J = 13.2 Hz, 3 J = 13.2 and 3.2 Hz, H-3a), 0.97 (s, 3H, CH 3 -18), 0.91 (s, 3H, CH 3 -20); 13 C NMR d 209.Propyl 7b-hydroxy-6-oxovouacapan-17b-oate (6): (171 mg, 88 %); white solid; m.p. 84.6-86.2 °C; Anal.…”
mentioning
confidence: 99%
“…Coumarins are known to inhibit photosynthetic phosphorylation, glycolysis and oxidative phosphorylation. A study showed that coumarins caused significant reduction of growth of some herbs including velvetleaf, pigweed and prosomillet and of another weed Amaranthus retroflexus . Inhibition of growth of some weeds including pigweed, coffeweed and barnyard grass was also induced by saponins in another sudy .…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of secondary metabolites produced by plants, such as essential oils are endowed with antimicrobial, allelopathic, antioxidant and bioregulatory molecules (French, 1985;Elakovich, 1988). Many of the essential oils and their constituents are commonly used as culinary herbs and spices (Isman, 2000).…”
Section: Discussionmentioning
confidence: 99%